Early pregnancy meal tolerance test responses and their association with later insulin sensitivity in overweight and obese women: an exploratory analysis - Arum, Puspito; Kdekian, Anoush; Lutgers, Helen L.; Gordijn, Sanne J.; Veenstra, Maaike K.; Sietzema, Maaike; Kruit, Janine K.; van der Beek, Eline M. (Frontiers in Endocrinology, 2026)
IntroductionInsulin resistance increases the risk for gestational diabetes mellitus (GDM) and hyperglycemia-associated pregnancy complications. GDM is generally diagnosed at 24–28 weeks of gestation, leaving limited time to address adverse consequences. To explore metabolic markers that predict changes in insulin sensitivity and glycemic responses earlier in pregnancy, we performed a meal tolerance test (MTT) during the early and late second trimester in an at-risk population.MethodsWe included 30 pregnant women with overweight or obesity in the Pregnancy Outcomes and Maternal Insulin Sensitivity (PROMIS) study. Glucose, insulin, and C-peptide levels were measured in fasted and post-challenge blood samples between week 12-16 (MTT1, n=26), week 24-25 (MTT2, n=21), and by an oral glucose tolerance test in week 26-27 (OGTT, n=19) of gestation. Pearson’s correlation test, Spearman’s correlation test, and linear regression were applied to evaluate the association between parameters at early and late time points.ResultsFasting insulin and C-peptide at MTT1 were associated with insulin resistance measured by Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) later in pregnancy (r=0.752, p<0.001; and r=0.825, p<0.001, respectively). Post-challenge increase in glucose, insulin, and C-peptide following MTT1 correlated with HOMA-IR in the late second trimester (r=0.626, p=0.009; r=0.739, p=0.002, and r=0.579, p=0.024, respectively). HOMA-IR and Matsuda index at MTT1 correlated with late second trimester HOMA-IR (r=0.781, p<0.001; and r=-0.826, p<0.001 respectively). Sixty, 90, and 120 minutes- post-challenge glucose during MTT2 correlated with 2 h-glucose during the OGTT (r=0.633, p=0.009; r=0.782, p<0.001, and r=0.639, p=0.008).DiscussionIn the early second trimester, fasting insulin and C-peptide might be suitable to stratify women early for GDM risk. The correlation between the MTT and OGTT results supports further exploration of the MTT as a patient-friendly alternative for diagnostic purposes.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT04315545, identifier NCT04315545.